IMPLIKASI PENERAPAN HUKUM PIDANA ADAT DALAM PENYELESAIAN TINDAK PIDANA PASCA PEMBARUAN HUKUM PIDANA NASIONAL INDONESIA - Tene, Damianus Rama; Muliyono, Andi; Lahangatubun, Nurjanah (Institut Agama Islam Negeri (IAIN) Bone, 2023)
Customary criminal law is a key component of Indonesia's legal framework, originating from the nation's indigenous culture. The process of reforming criminal law in Indonesia, which aims to replace the old colonial criminal law, has included elements of customary criminal law as the legal basis and recognition of them in the latest revision of the